The banker's wife [large type] - Alger, Cristina (Thorndike Press, a part of Gale, a Cengage Company, 2018)
"On an early November morning, a couple boards a plane bound for Geneva. Soon after, it drops off the radar and the wreckage is later discovered in the Alps. Among the missing is Matthew Lerner, an insider at Swiss United, a powerful offshore bank. His young widow, Annabel, is left grappling with the secrets he left behind, including an encrypted laptop and a shady client list. Desperately searching for answers, she determines that Matthew's death was no accident--and that she is now in the crosshairs of his powerful enemies."--Back cover.